Educating gazes that offer resistance to the coloniality of seeing - Zárate Moedano, Rodrigo (2019)
This article systematizes the learning experiences developed by members of a film analysis community of practice whose purpose was to educate gazes to offer resistance to the coloniality of seeing. It describes the theoretical foundations of decolonial audiovisual literacy, and the political-pedagogical project from which the education process was promoted. In addition, it presents the films that were analyzed and the criteria that guided the selection process. It explains from which assumptions and in which way the systematization of experiences was carried out by facilitators and apprentices participating in the Sound Film Grammar subject of the Specialization in Film Studies (EEC) of the University of Veracruz (Mexico): a graduate program where apprentices from diverse academic disciplines participate. By presenting empirical evidence of the apprentices’ voices and gazes, it describes an innovative educational experience due to the diverse profile of the apprentices; the academic, institutional and national framework in which it took place; and the integration of critical perspectives of film studies, visual studies, media education and education aimed at building interculturality and decoloniality.